2017
DOI: 10.1038/s41598-017-00912-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel 4-arm DNA/RNA Nanoconstruct triggering Rapid Apoptosis of Triple Negative Breast Cancer Cells within 24 hours

Abstract: Measuring at ~30 nm, a fully customizable holliday junction DNA nanoconstruct, was designed to simultaneously carry three unmodified SiRNA strands for apoptosis gene knockout in cancer cells without any assistance from commercial transfection kits. In brief, a holliday junction structure was intelligently designed to present one arm with a cell targeting aptamer (AS1411) while the remaining three arms to carry different SiRNA strands by means of DNA/RNA duplex for inducing apoptosis in cancer cells. By carryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…The selection for these cell types (MDA-MB 231, AGS and Hec1A) was due to their distinctive cell morphological shape under normal culture conditions. For instance, healthy MDA-MB 231 cells typically adopt a "needle-like" cell morphology 65 while AGS cells normally present a polygonal shape while adhering to surfaces 66 . On the other hand, Hec1A is often roundish in morphology without any distinctive polarity or directionality and are not very highly adherent cells 35,67 .…”
Section: X-ray Photoelectron Spectroscopy (Xps) Analysis and Atomic Fmentioning
confidence: 99%
“…The selection for these cell types (MDA-MB 231, AGS and Hec1A) was due to their distinctive cell morphological shape under normal culture conditions. For instance, healthy MDA-MB 231 cells typically adopt a "needle-like" cell morphology 65 while AGS cells normally present a polygonal shape while adhering to surfaces 66 . On the other hand, Hec1A is often roundish in morphology without any distinctive polarity or directionality and are not very highly adherent cells 35,67 .…”
Section: X-ray Photoelectron Spectroscopy (Xps) Analysis and Atomic Fmentioning
confidence: 99%
“…The results demonstrated a downregulation of the three gene targets, an upregulation of phospho-p53 which subsequently led to reduced cell survival within 24 h at a very low dose. This particular four-arm nanoconstruct of the holiday junction was reported to represent a potential contender for designing gene antisense therapy [23]. These studies suggested that therapeutics using genomic techniques including miRNA or RNAi, targeting key genes involved in drug resistance, combined to nanocarrier particles are viable approaches in the treatment of breast cancer patients.…”
mentioning
confidence: 99%
“…As stated previously, in order to examine the cytotoxicity of the various surfaces, the three different cell types were incubated on all surfaces, and the cell viability was determined via a colorimetric based cell viability kit, performed after 24 h of incubation ( n = 5). At this junction, it is also important to state that we selected these cell types for their differing adhesion morphologies on surfaces in general, with MDA-MB 231 exhibiting good spreading morphology [ 28 ] and HEC1A having a rounder overall morphology [ 29 ]. Prior to confocal microscopy and cell viability data discussion, it may be necessary to state that the correlation between cell counts from fluorescence and cell viability does not always exhibit a directly proportional relationship.…”
Section: Resultsmentioning
confidence: 99%